Early developmental exposure to air pollution increases the risk of Alzheimers disease and amyloid production: Studies in mouse and Caenorhabditis elegans: Molecular and cell biology/APP/Abeta/amyloid. (7th December 2020) - Haghani, Amin; Johnson, Riachard G.; Dalton, Hans; Feinberg, Jason I.; Lewis, Kristy C.; Ladd‐Acosta, Christine; Woodward, Nicholas C.; Safi, Nikoo; Jaffe, Andrew E.; Allayee, Hooman; Sioutas, Constantinos; Campbell, Daniel B.; et al.
Abstract: Background: Exposure to air pollution (AirP) as adults increases the risk for dementia in human populations and increases the production of amyloid‐beta peptides in mouse models (Cacciottolo et al 2017 PMID28140404). Gestational exposure to AirP adversely alters early human neurodevelopment and increases risk for cognitive and behavioral disorders. It is unknown if gestational or developmental exposure to AirP can increase the risk for or accelerate cognitive aging or Alzheimer's disease (AD) in later adulthood. Methods: To approach this gap, we examined the developmental effects of nano‐sized urban particulate matter (nPM), a subfraction of AirP, on later life stages of mice and nematodes. In C57BL/6J mice, initial transcriptional changes in the cerebral cortex or hippocampus were studied by RNAseq and tested for association with long‐lasting phenotypic effects of gestational nPM exposure. Experiments on Caenorhabditis elegans addressed developmental effects of nPM on AD‐related genes and Aß production in later adulthood. Results: Gestational exposure to nPM caused sex‐specific gene expression changes in the cerebral cortex of pups at postnatal day 5. The changes included DNA damage, oxidative stress, and immune responses. The top potential upstream regulators of these transcriptome changes included APP, Psen1, and Tau. At age 5 months, neuroinflammatory gene expression in the hippocampus was associated with depressive behavior, weight and fat gain, and increased glucose intolerance. Similarly, the initial responses of the L1 larval stage of C. elegans to nPM included an increase of mRNA levels in genes related to inflammation (e.g. abf‐2 ) and AD‐gene homologs (e.g. sel‐12 /PSEN1). In an AD nematode model, developmental exposure to nPM in the L1 stage resulted in an accelerated paralysis phenotype in adults which is an indicator of increased Aß42 production. Conclusions: This novel experimental evidence suggests mechanisms by which the developmental exposure to AirP could increase AD risk in later ages. Further studies may reveal the effects of gestational nPM exposure on later‐life cognition, Aß plaque formation, and neuropathology.